Neural activation and memory for natural scenes: Explicit and spontaneous retrieval. (6th May 2018) - Weymar, Mathias; Bradley, Margaret M.; Sege, Christopher T.; Lang, Peter J.
Abstract: Stimulus repetition elicits either enhancement or suppression in neural activity, and a recent fMRI meta‐analysis of repetition effects for visual stimuli (Kim, 2017) reported cross‐stimulus repetition enhancement in medial and lateral parietal cortex, as well as regions of prefrontal, temporal, and posterior cingulate cortex. Repetition enhancement was assessed here for repeated and novel scenes presented in the context of either an explicit episodic recognition task or an implicit judgment task, in order to study the role of spontaneous retrieval of episodic memories. Regardless of whether episodic memory was explicitly probed or not, repetition enhancement was found in medial posterior parietal (precuneus/cuneus), lateral parietal cortex (angular gyrus), as well as in medial prefrontal cortex (frontopolar), which did not differ by task. Enhancement effects in the posterior cingulate cortex were significantly larger during explicit compared to implicit task, primarily due to a lack of functional activity for new scenes. Taken together, the data are consistent with an interpretation that medial and (ventral) lateral parietal cortex are associated with spontaneous episodic retrieval, whereas posterior cingulate cortical regions may reflect task or decision processes.